Utilization Of Buckwheat, Proso Millet, And Amaranth For A Gluten-Free Cereal Bar - Ojha, Pravin; Adhikari, Anuska; Manandhar, Utshah; Maharjan, Sushma; Maharjan, Sophi (Department of Technology of Agricultural product (THP) Jambi University, 2022)
Four formulations of cereal bar were prepared using common buckwheat (55 parts), proso millet (15-30 parts), white amaranth (25-40 parts), walnut (27.5 parts), and jaggery (50 parts), by varying the proportions of proso millet and white amaranth in the ratio of 15:40, 20:35, 25:30 and 30:25. Roasted cereals and walnut pieces were mixed with jaggery syrup of 73.7Â° Bx and baked at 120Â° C for 20 minutes. The bars' proximate composition, mineral content (Ca, Fe and P) were evaluated and compared with the bar available in the market. The textural analysis and sensory profile of the bar were also evaluated. The crude fiber, calcium, and iron were significantly higher (p<0.05) in formulated bars compared to the market sample while energy and fat content were significantly higher (p<0.05) in the market sample. The formulated bars provided 440.31- 489.81kcal energy per 100 g, which qualified the product as a good energy-dense snack. From the textural analysis and sensory evaluation, Formulation C (common buckwheat-55, proso millet-25, white amaranth-30, walnut-27.5, and jaggery-50) was harder and preferred the most based on taste and overall acceptability. The research concludes the good potentiality of underutilized crops for cereal bar production.